2017
DOI: 10.26740/jp.v2n1.p70-76
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Berbasis SETS (Science, Environment, Technology, Society) Terintegrasi Nilai Islam di SMAI Surabaya pada Materi Ikatan Kimia

Abstract: AbstrakTujuan penelitian ini adalah: (1) Pengembangan produk modul kimia berbasis SETS terintegrasi nilai islam pada materi ikatan kimia, (2) Mengetahui kelayakan modul kimia berbasis SETS terintegrasi nilai islam, (3) Mengetahui keefektifan keterterapan modul kimia berbasis SETS terintegrasi nilai islam. Produk yang dikembangkan dalam penelitian ini adalah modul kimia berbasis SETS terintegrasi nilai islam pada materi ikatan kimia. Spesifikasi modul kimia berbentuk media cetak sebagai implementasi kurikulum 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 1 publication
(1 reference statement)
0
8
0
4
Order By: Relevance
“…The purpose of the SETS learning is to enable students to understand science better, encourage them to improve their creative and critical thinking skills, and make boring and abstract topics more exciting and enjoyable (Aikenhead, 1994). Previous studies have revealed that the SETS implemented in chemistry learning has possessed a significant impact on learning outcomes (Imaduddin, 2013;Rahmah, Mulyani, & Masyikuri, 2017). Further, they have found a difference amongst critical thinking skills of students, who took the SETSbased guided inquiry, guided inquiry learning, and conventional learning (Jariyah, 2017;Nisak, Wartono, & Suwono, 2017).…”
Section: Science Environment Technology and Society (Sets) Approacmentioning
confidence: 99%
“…The purpose of the SETS learning is to enable students to understand science better, encourage them to improve their creative and critical thinking skills, and make boring and abstract topics more exciting and enjoyable (Aikenhead, 1994). Previous studies have revealed that the SETS implemented in chemistry learning has possessed a significant impact on learning outcomes (Imaduddin, 2013;Rahmah, Mulyani, & Masyikuri, 2017). Further, they have found a difference amongst critical thinking skills of students, who took the SETSbased guided inquiry, guided inquiry learning, and conventional learning (Jariyah, 2017;Nisak, Wartono, & Suwono, 2017).…”
Section: Science Environment Technology and Society (Sets) Approacmentioning
confidence: 99%
“…Tujuan yang harus dicapai oleh anggota KIR secara individual adalah pengembangan sikap ilmiah, kejujuran dalam memecahkan gejala alam yang ditemui dengan kepekaan yang tinggi dalam metode yang sistematis, objektif, rasional dan berprosedur sehingga akan didapatkan kompetensi untuk mengembangkan diri dalam kehidupan (Susilowarno, 2003). (Rahmah, Mulyani, & Masyikuri, 2017). Pemikiran yang kritis sangat diperlukan untuk belajar setiap elemen SETS dengan memperhatikan berbagai keterkaitan antara unsur-unsur SETS yaitu sains, lingkungan, teknologi dan hal-hal lainnya yang berkenaan dengan masyarakat (Afriawan, Binadja, & Latifah, 2012).…”
Section: Pendahuluanunclassified
“…(2016) that chemistry teaching materials with the integration of spiritual values also do not reduce the scientific level. The use of chemical modules with the integration of Islamic values has also been shown to show better learning outcomes than conventional learning (Rahmah, 2017). Various development of this teaching material proves that the integration of spiritual values is very feasible to do because it does not reduce the scientific level of teaching materials and has succeeded in increasing student learning activities and outcomes, as well as the students' character values.…”
Section: Introductionmentioning
confidence: 98%
“…Analysis of various articles that have been published in various journals on chemistry teaching materials with Islamic internalization values or verses of Al-Qur'an has been carried out, including in petroleum material (Faeha, dkk., 2019), colloids (Usman, dkk., 2017), thermochemistry (Fitriani, dkk., 2016), and chemical bonds (Rahmah, 2017). Faeha, dkk.…”
Section: Introductionmentioning
confidence: 99%